Internalisasi Pembelajaran Toleransi Beragama Dalam Meningkatkan Prestasi Peserta Didik di Madrasah Ibtidaiyah - Veri Ikra Mulyadi (Journal of Islamic Education and Learning, 2022)
This study aims to analyze the process of internalizing religious tolerance learning in improving student achievement in an elementary school. The background of this study is based on the importance of tolerance values ??as part of character education that can create a harmonious and conducive learning environment. Religious tolerance in Islamic elementary schools is crucial in forming an attitude of mutual respect for differences, as well as a foundation in building optimal learning achievement. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects of the study included the head of the madrasah, Islamic Religious Education teachers, and students in grades V and VI at an elementary school in East Java. The results of the study showed that internalization of religious tolerance learning was carried out through the integration of tolerance values ??in subjects, teacher role models, joint religious activities, and an inclusive school culture. The implementation of these tolerance values ??contributed positively to improving student achievement, both in terms of cognitive, affective, and social aspects. Students showed an increase in enthusiasm for learning, ability to work together, and control conflict between friends. Thus, it can be concluded that learning religious tolerance that is internalized systematically and sustainably plays an important role in creating an educational environment that supports the achievement of academic achievement and character formation of students.